EFFECTIVENESS OF CHICKEN MANURE AND ARTHROBOTRYS DACTYLOIDES ON THE SUPPRESSION OF MELOYDOGYNE JAVANICA - Sudirman . (CROP AGRO, Scientific Journal of Agronomy, 2011)
ABSTRACT The suppression of Meloidogyne javanica with the application of kaolin alginate formulated Arthrobotrys dactyloides and chicken manure was investigated. The aims of the study were to know the effects of chicken manure on the growth, ring production, trapping activity of A. dactyloides, and suppression of M. javanica, as well as plant growth. A series of experiments consisted of slide test, soil microcosms, and pot tests were conducted with six dosages of chicken manure; 0.25%, 0.50%, 0.75%, 1.00%, 1,25%, and 1,50% (w/w) with five replicates. Treatment without chicken manure was provided as a control. All experiments were conducted with completely randomized design. The data were analyzed with analysis of variance, and means of each treatment were separated using a honestly significant difference test at 5% level. Results of the study showed that chicken manure did not have significant effect on the growth, ring production, and trapping activity of A. dactyloides, a fungus that effectively reduced number of nematodes entering roots of tomato seedlings. However, chicken manure significantly reduced number of M. javanica penetrating roots, hampered M. javanica development, and improved plant growth. ABSTRAK Penekanan M. javanica dengan aplikasi A. dactyloides dalam formulasi kaolin alginate dan pupuk kotoran ayam telah diteliti. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh pupuk kotoran ayam terhadap pertumbuhan, pembentukan cincin perangkap, aktifitas penjeratan A. dactyloides, dan penekanan M. javanica, serta pertumbuhan tanaman tomat. Serangkaian percobaan yang terdiri dari “slide test”, “soil microcosms”, dan percobaan pot telah dilakukan dengan enam dosis pupuk kotoran ayam; 0.25%, 0.50%, 0.75%, 1.00%, 1,25%, dan 1,50% (b/b) dengan lima ulangan. Perlakuan tanpa pupuk disiapkan sebagai control. Semua percobaan dilaksanakan dengan rancangan acak lengkap. Data dianalisa dengan analisis keragaman dan dilanjutkan dengan uji beda nyata jujur pada taraf nyata 5%. Hasil penelitian menunjukkan bahwa pupuk kotoran ayam tidak berpengaruh nyata terhadap pertumbuhan, pembentukan perangkap, dan penjeratan M. javanica oleh A. dactyloides, jamur yang secara efektif menekan jumlah M. javanica yang penetrasi ke dalam akar tanaman tomat.Tetapi, pupuk kotoran ayam secara nyata mengurangi jumlah M. javanica yang penetrasi akar, menekan perkembangan nematoda, dan meningkatkan pertumbuhan tanaman.